ENHANCING LEGAL CERTAINTY AND INSTITUTIONAL MODELS FOR HALAL CERTIFICATION IN INDONESIA'S FOOD AND BEVERAGE SECTOR - Asro, Muhammad; Sofyan, Ayi (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2021)
The implementation of Law No. 33 of 2014 on Halal Product Assurance (Jaminan Produk Halal, JPH) in Indonesia highlights significant challenges in legal protection and institutional frameworks. These include public awareness gaps about the halal certification process, lack of compliance among certified entities, and the delayed establishment of the Halal Product Assurance Agency (BPJPH), which became operational in October 2017 but has not yet fully met its mandate. This study aims to develop an institutional model for implementing Article 4 of the Halal Product Assurance Law, focusing on the food and beverage sector in Indonesia. It also explores the philosophical underpinnings of halal principles (halalan tayyiban) in alignment with Qur'anic guidance (Q.S. Al-Baqarah: 168) and modern medical insights on health and well-being. Employing a normative-empirical legal research approach, this study utilizes descriptive qualitative analysis to synthesize regulatory frameworks, empirical findings, and philosophical insights, concluding with inductive reasoning to propose practical solutions. Findings indicate that BPJPH's implementation of the JPH Law remains suboptimal due to insufficient numbers of authorized Halal Product Institutions (LPHs). Moreover, the transition from a voluntary to a mandatory halal certification system introduces critical legal and procedural shifts, including new obligations, validity periods, and auditing requirements. These challenges underline the need for policy adjustments to ensure legal certainty and effective governance.